1981
DOI: 10.1073/pnas.78.5.2747
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the gene coding for Escherichia coli DNA topoisomerase I affect transcription and transposition.

Abstract: Mutations in top, the structural gene for Escherichia coli DNA topoisomerase I, have been identified and mapped at 28 min on the chromosome, near cysB. Strains carrying deletions of the top gene are viable. The top mutations, however, do exert pleiotropic effects on transcription and transposition. Mutants lacking DNA topoisomerase I have a more rapid rate of induction and a higher level of catabolite-sensitive enzymes including tryptophanase and -galactosidase. This general activation of transcription by top … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
156
2

Year Published

1985
1985
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(163 citation statements)
references
References 41 publications
5
156
2
Order By: Relevance
“…Type I topoisomerase, first described in prokaryotes by Wang (1971) and in eukaryotes by Champoux and Dulbecco (1972) and later characterized by Keller (1975a, b), change the linking number in steps of one. Although their biological function is not completely defined , this class of topoisomerase has been implicated in transcriptional (Akrigg and Cook 1980;Dynan and Burgess 1981;Sternglanz et al 1981;Weisbrod 1982;Fleischmann et al 1984 ;Gilmour et al 1986;Shastry 1986) as well as in recombinational and replicational (Kikuchi and Nash 1979 ;Sternglanz et al 1981 ; also see Gellert 1981 ;Bullock et al 1985 ;Zeng et al 1985) events. J n higher eukaryotes topoisomerase I is enriched in the nucleolus (Fleischmann et al 1984;Muller et al 1985) and may play a role in transcription of supercoiled rDNA in vitro (Garg et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Type I topoisomerase, first described in prokaryotes by Wang (1971) and in eukaryotes by Champoux and Dulbecco (1972) and later characterized by Keller (1975a, b), change the linking number in steps of one. Although their biological function is not completely defined , this class of topoisomerase has been implicated in transcriptional (Akrigg and Cook 1980;Dynan and Burgess 1981;Sternglanz et al 1981;Weisbrod 1982;Fleischmann et al 1984 ;Gilmour et al 1986;Shastry 1986) as well as in recombinational and replicational (Kikuchi and Nash 1979 ;Sternglanz et al 1981 ; also see Gellert 1981 ;Bullock et al 1985 ;Zeng et al 1985) events. J n higher eukaryotes topoisomerase I is enriched in the nucleolus (Fleischmann et al 1984;Muller et al 1985) and may play a role in transcription of supercoiled rDNA in vitro (Garg et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, topoisomerase I is not essential: deletion mutants are viable (22). However, topoisomerase I deletion mutants of Escherichia coli grow well only because they have acquired compensatory mutations (7,23).…”
mentioning
confidence: 99%
“…Shortly after the identification of a set of viable E. coli ⌬topA mutants (25), it was found that the ⌬topA locus of these mutants could not be readily transduced into strain PLK831 (⌬trpE63 pyrF287 nirA trpR72 iclR7 gal25 rpsL195) by phage P1 (26,27). The same recipient strain became more easily transduced, however, if it had acquired a compensatory change within certain regions of the E. coli chromosome, including gyrA and gyrB, which encode the two subunits of gyrase, and a region containing tolC, which encodes an outer membrane transporter (26 -29).…”
mentioning
confidence: 99%